Thrombophilia Screening in Young Patients With Cryptogenic Ischemic Stroke - Abels, Sofie; Sihvo, Maximillian; Tomppo, Liisa; Kutal, Shakar; Martinez-Majander, Nicolas; Tulkki, Lauri; Sarkanen, Tomi; Jäkälä, Pekka; Redfors, Petra; Huhtakangas, Juha; Ylikotila, Pauli; von Sarnowski, Bettina; et al. (Ovid Technologies (Wolters Kluwer Health), 2026)
Background: The incidence of cryptogenic ischemic stroke (CIS) in young adults is increasing, particularly among those without traditional vascular risk factors. Thrombophilia may contribute to CIS pathogenesis, yet guidelines differ on the relevance of screening. We investigated the sex-specific prevalence of routinely applied thrombophilia screening in young-onset CIS and its association with clinical characteristics and standard laboratory results.
Methods: We included young patients with CIS aged 18 to 49 years from the SECRETO study (Searching for Explanations for Cryptogenic Stroke in the Young: Revealing the Triggers, Causes, and Outcome). Routinely used thrombophilia panels obtained at admission and repeated testing within 1 year of stroke were analyzed. Ten thrombophilia markers were assessed and categorized according to the grade of deviation into lowest, low, and high thrombosis risks. Factors associated with any deviation in thrombophilia markers were investigated with multivariable logistic regression.
Results: Of 598 initially enrolled patients with CIS, 556 undergoing baseline thrombophilia testing were analyzed (median age, 41.0 [interquartile range, 34.1-45.8] years; male:female ratio 1.2:1). Of these, 120 (21.6%) and 36 (6.5%) were retested by 3 and 12 months, respectively. At baseline, any thrombophilia abnormality was observed in 206 patients (37.1%; men, 38.2%; women, 35.7%). High-risk thrombophilia was identified in 29 patients (5.2%) at baseline, in 13 retested patients (11.1%) at 3 months, and in 5 retested patients (13.9%) at 12 months. Overall, 45 patients (8.1%) had persistent thrombophilia abnormalities (men, 7.9%; women, 8.3%). Physical inactivity, a history of venous thromboembolism, low HDL (high-density lipoprotein)-cholesterol, and low hemoglobin were associated with any deviation in the thrombophilia markers. Anticoagulation was initiated in 50.0% of patients with abnormal baseline thrombophilia versus 35.7% without (P=0.042) and in 26.9% versus 6.2% with and without persistent abnormalities (P<0.001).
Conclusions: Over a third of young adults with CIS had thrombophilia deviations at admission although high-risk thrombophilia results remained rare. Screening may be considered in young patients with CIS with a history of venous thromboembolism, physical inactivity, and low hemoglobin or HDL-cholesterol.
Keywords: adult; case-control studies; ischemic stroke; risk factors; stroke; thrombophilia.